Reproductive biology aspects of two species of the genus Gavilea (Orchidaceae, Chloraeinae) in populations from Central Chile Aspectos de la biología reproductiva de dos especies del género Gavilea (Orchidaceae, Chloraeinae) en poblaciones de Chile central - Carlos E Valdivia (Universidad de Concepción, 2010)
The extent to which plants depend on pollinators for outcross pollen transportation is a key issue in plant reproductive ecology. We evaluated the putative breeding system, foral display, and natural pollination in two Southern Cone of South American orchids, Gavilea araucana and G. venosa, by performing four hand pollination trials (agamospermy, autogamy, geitonogamy, and xenogamy tests) and by counting each fower and fruit produced by plants in natural conditions. Fruit set differed signifcantly depending on the origin of pollen as well as on the presence of a pollen vector. None of these species produced fruits by the agamospermy tests, therefore indicating that they require the presence of pollen on the stigmas for fruit setting. By contrast, only G. araucana was capable of fruit setting following the autogamy test, therefore demostrating that this orchid needs not depend on pollinators for fruit set. Furthermore, G. araucana and G. venosa produced 100% fruits by geitonogamy and by xenogamy, thereby indicating that both plants are totally self-compatible. The mean number of fowers per plant was 2.1 times higher in G. venosa with respect to G. araucana; however, natural fruiting success was 28.8% and 98.9%, respectively. Furthermore, while the increase in fruiting success signifcantly and positively correlated with an increase in foral display in G. araucana, in G. venosa these variables were unrelated. Certainly, further studies concerning the reproductive strategies in orchids of southern South America are of great importance. El alcance al cual las plantas dependen de polinizadores para el transporte de polen para los exocruzamientos es uno de los temas claves en ecología reproductiva de las plantas. Evaluamos el sistema reproductivo potencial, despliegue foral y polinización natural en dos orquídeas del Cono Sur de Sudamérica, Gavilea araucana y G. venosa, efectuando cuatro ensayos de polinización manual (agamospermia, autogamia, geitonogamia y xenogamia) y contando cada for y fruto producidos por las plantas en condiciones naturales. La producción de frutos difrió signifcativamente dependiendo del origen del polen así como de la presencia de un vector polínico. Ninguna de las especies produjo frutos en las pruebas de agamospermia indicando, por lo tanto, que ellas requieren de la presencia de polen en los estigmas para producir frutos. Por el contrario, solamente G. araucana fue capaz de producir frutos siguiendo la prueba de autogamia demostrando, por ende, que esta orquídea no necesita depender de polinizadores para producir frutos. Además, G. araucana y G. venosa produjeron un 100% de frutos por geitonogamia y xenogamia, indicando esto, que ambas plantas son autocompatibles. El número promedio de fores por planta fue 2,1 veces mayor en G. venosa con respecto a G. araucana; sin embargo, el éxito en la fructifcación natural fue de 28,8% y 98,9%, respectivamente. Además, mientras el incremento en el éxito de la fructifcación se correlacionó positiva y signifcativamente en G. araucana, en G. venosa estas variables no estuvieron relacionadas. Ciertamente, estudios adicionales referidos a las estrategias reproductivas de las orquídeas del sur de Sudamérica son de gran importancia.